'Let us make Zimbabwe in my own name': Place naming and Mugabeism in Zimbabwe. Issue 1 (2nd January 2020) - Mamvura, Zvinashe
Abstract : This article adopts a scalar perspective to explore the social construction of cultural geographies that communicate a political ideology that the Mugabe regime created in Zimbabwe. It examines scale-related politics as a governmental institutional political practice which the Mugabe regime executed in order to create and institutionalise a Mugabe personality cult in Zimbabwe, widely known in the literature as Mugabeism. In Zimbabwe, the name Robert Mugabe features the most in the cultural landscape when compared to any other Zimbabwean political actor. This cannot be politically innocent or neutral. Toponymic inscription is critical in creating politically charged linguistic landscapes which communicate intended political agendas. Place names are part of the linguistic tokens that constitute the linguistic landscape. The general public's conceptualisation of reality is partly shaped by information that comes to them in visual form. This article deploys the three facets of scale, as they relate to the components of the built environment, namely size, level and relation. Through adopting a scalar lens, this article interrogates toponymic strategies that the Mugabe regime employed in order to spatialise Mugabe's political power.